Analysis of Hybrid Optical Modulation Technique with Multicast and Unicast System - Singh, Akanksha (My University, 2019)
In past few years the optical fiber communication system is becoming the area of interest because of the several advantages provided due to which it is used in satellite communication, aircrafts and under water communication etc. During the transmission of a signal through channel the essential purpose of optical fiber communication system is to use minimum bandwidth and also to enlarge the spectral efficiency of the overall system. The spectral efficiency of the overall system can be enlarged by adopting the polarization multiplexing techniques together with Quadrature Amplitude Modulation (QAM) and Quadrature phase shift keying (QPSK). The system capacity can be upgraded by using orthogonal polarization between nearby WDM channel. However, the birefringence caused due to depolarization of the orthogonal states which may cause the signal to dissipate which in turn reduces the overall capacity of the and system bandwidth. The intension of the thesis is to scrutinize the performance of hybrid optical modulation techniques with multicast system and unicast system and to achieve this target optisystem v15 simulation software is used which facilitates the user to design the different types of simulated models. Firstly, to investigate the performance of hybrid modulation techniques in optical domain with multicast system and unicast system, we first need to study the different modulation techniques with their modulation and demodulation parts. When different modulation techniques are studied then the user needs to analyse their performance in terms of Bit Error Rate (BER), Power input and Q-factor etc. These modulation scheme are then combined to make one single technique, this is known as hybrid modulation technique. The advantage of hybrid technique is that it offers ease of security with high data rate transmission using minimum bandwidth so as to make a cost effective architecture. The first model as depicted in chapter 3 is investigated using NRZ, DQPSK and PolSK as unicast data and DPSK as multicast data transmission. In this research work, the data rate of unicast is 1090Gbps, the length of the optical fiber used is 50Km and number of loops is 10 therefore, the overall fiber length is 500Km. The outstanding OSNR is observed for NRZ+DQPSK+PoLSK which are 26dBm at 7x10-4. The second model is analysed by using DPSK multicast data and NRZ+DQPSK+DP-16QAM as unicast data. In this proposed work, the generated data rate of unicast data is 1690Gbps with 15GHz of channel spacing in every sub channel. The superlative OSNR is examined for unicast data (NRZ+DP-16QAM+DQPSK) which is 26dBm at a distance of 6.8x10-4. The optical fiber used is 50Km and loop control comprises of 8 loops therefore the total distance for the proposed work is 400Km. The last model manifests the implementation of multicast and unicast system with Nyquist super channel. The modulation schemes used for unicast data transmission are Nyquist DP-16QAM with PolSK providing data rate of 640Gbps and 40Gbps data rate for DPSK multicast data. The foremost OSNR is for unicast data (Nyquist DP-16QAM) which is 26dBm at 7x10-4.The length of the optical fiber used is 50Km and the number of N recirculating loops are 10threfrore the overall distance covered is 500Km.
Keywords: Hybrid Modulation; Muticast; Unicast